Exploring Strategies to Build Resiliency in Nurses During Work Hours. (April 2021) - Mintz-Binder, Ronda; Andersen, Susan; Sweatt, Laura; Song, Huaxin
Abstract : OBJECTIVE: This pilot study investigated increasing nurse resiliency utilizing a toolkit of stress-reducing interventions on medical-surgical units at 4 hospitals. BACKGROUND: Resiliency-building activities are time consuming and undertaken outside work hours. Although the activities show a positive impact on resilience, researchers investigated whether similar results could be achieved where nurses experience work stress. METHODS: This quasi-experimental pretest and posttest interventional study used a within-subjects design. Provided toolkits included written instructions to carry out the study. Nurses completed surveys at baseline, at 10 time points over a 6-week period, and at study conclusion. RESULTS: The Connor-Davidson Resilience Scale-10 scores increased significantly at follow-up ( P < .02). Self-reported stress levels decreased over the 10 shifts with continued use of the interventions. CONCLUSION: Using stress-reducing interventions during work decreased stress and increased resiliency, thereby offering nurse leaders additional options to promote a healthy workforce at the bedside.